EFFECT OF SUPPLEMENTAL FEEDING ON THE WEIGHT OF SILK GLANDS AND LARVAL DEVELOPMENT OF MULBERRY SILKWORM (Bombyx mori) - MUHAMMED , HELAN ABDUL WAHAB; AYOUB, ZAHRA NAEEF (Journal of Duhok University, 2023)
The study aimed to revive the Sericulture in our area after three decades of absence and to investigate the role of supplemental feeding on silk glands, larval growth, and some economic traits of cocoons of mulberry silkworms (Bombyx mori). Larvae of 5th instar fed on vitamin C during their 4th and 5th instars showed a significant increase in their length (6.953 ± 0.248 mm). Mature larvae fed on vitamin C showed a significant increase in their weight (3.690±0.129 g). Vitamin C was the most effective supplement for the stimulation of silk gland growth. Larvae fed on vitamin C showed a significant increase in their cocoon weight (2.158 ± 0.131 g) followed by those fed on honey (2.126 ± 0.156 g). Only cocoons fed as larvae on vitamin C showed a significant increase in their length (3.793 ± 0.125 cm). Larvae fed on vitamin C showed a significant increase in their cocoon width (1.873 ± 0.050 cm). Feeding silkworms during their 4th and 5th instars on mulberry leaves sprayed with vitamin C was more effective in stimulating larval growth, silk glands and improving economic characteristics of silk cocoons